Synthesis and characterization of a hierarchically structured three-dimensional conducting scaffold for highly stable Li metal anodes - Kim, Ji Young; Liu, Guicheng; Tran, Minh Xuan; Ardhi, Ryanda Enggar Anugrah; Kim, Hansung; Lee, Joong Kee (ROYAL SOC CHEMISTRY, 2019)
Herein, the lithiophilicity of Li2O and the capillary action-induced absorption of molten Li are employed to fabricate a hierarchically structured three-dimensional (3D) Li metal electrode comprising Li2O-coated Cu foam (Li2O@Cu foam), the unique structural characteristics of which allow one to suppress Li dendrite formation and confine Li movement within the foam matrix. The lithiophilicity of Li2O@Cu foam is ascribed to the occurrence of in situ interfacial reactions between Li and Cu oxides formed on the surface of Cu foam, and the formation of the Li2O@Li@Cu hierarchical structure is shown to significantly stabilize the interfacial characteristics of the Li metal anode even in harsh electrochemical environments. In addition to being lithiophilic, Li2O@Cu foam allows for homogeneous plating and stripping of Li ions, since the nucleation overpotential of Li2O toward Li ions is low, e.g., the lowest overpotential of 13mV is observed during Li plating/stripping at 1.0 mA cm(-2). At a total capacity of 1.0 mA h cm(-2), Li2O@Cu foam exhibits a coulombic efficiency of >99.0% over 150 cycles at 0.5 mA cm(-2), whereas a slightly smaller value of approximate to 97.5% is observed for 100 cycles at 5 mA cm(-2).
Keywords: CURRENT COLLECTOR; LITHIUM; DEPOSITION; NANOWIRES; STABILITY; XPS